2015
DOI: 10.9734/bjast/2015/19001
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Accumulation in Water, Sediments and Catfish (Clarias gariepinus) from Two Fishing Settlements along River Kaduna in Niger State, Nigeria

Abstract: Freshwater is a vital medium by which fish for human consumption are cultured, thus, preserving its quality is essential. The presence and bioaccumulation pattern of some heavy metal concentrations in wild African Catfish, Clarias gariepinus (Burchell, 1822) muscles and water samples, collected from River Kaduna during the dry season month of December was assessed, to determine their concentrations, physico-chemical parameters, and risk evaluation of selected metals and their effects on fish quality. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
0
1
Order By: Relevance
“…The highest values were recorded in Clarias gariepinus, while the lowest values were in the Nile tilapia. These findings are matching with the previous results in Nigeria (Omozokpia et al, 2015). It was noticed that the recorded values of chromium in all fish did not exceed the internationally permitted levels (2.3 micrograms / gram) given by the FAO/WHO.…”
Section: Elements Distributionsupporting
confidence: 91%
See 1 more Smart Citation
“…The highest values were recorded in Clarias gariepinus, while the lowest values were in the Nile tilapia. These findings are matching with the previous results in Nigeria (Omozokpia et al, 2015). It was noticed that the recorded values of chromium in all fish did not exceed the internationally permitted levels (2.3 micrograms / gram) given by the FAO/WHO.…”
Section: Elements Distributionsupporting
confidence: 91%
“…The highest values of nickel were recorded in Clarias gariepinus, while the lowest value was in Dicentrarchus labrax, as shown in Table (1). These results are slightly higher than the previous results in Nigeria (Omozokpia et al, 2015). It was denoted that the recorded values of nickel in all fish exceeded by a large percentage the internationally permissible levels (0.03 micrograms /g) given by the FAO/WHO.…”
Section: Elements Distributioncontrasting
confidence: 63%
“…The protein content of charcoal smoked catfish (26.31%) is higher than gas smoked (24.28%). Similarly, Omozokpia et al (2015) also reported that protein contents increased with decrease in moisture content. However, the protein contents of tilapia fishes in this study 36.47% and 37.30% for charcoal and gas smoked, respectively are lower than that 48.87%, 49.40% and 64.90% after 15 hours of smoke-drying tilapia fishes at 50 o C, 60 o C and 70 o C, respectively (Idah and Nwankwo, 2013).…”
Section: Proximate Composition Of Fish Samplesmentioning
confidence: 81%